Multi-Omics Analysis After Vaginal Administration of Bacteroides fragilis in Chickens - Chen, Lu; Yang, Maosen; Zhu, Wei; Su, Yuan; Li, Diyan; Wang, Tao (Frontiers in Microbiology, 2022)
The reproductive tract of chickens is an important organ for egg formation. The vagina is in close contact with the external environment, which may lead to the invasion of a variety of pathogenic bacteria, affect the internal and external quality of eggs, and even increase mortality and cause economic loss. In recent years, probiotics as a substitute for antibiotics have brought economic benefits in livestock and poultry production. In the present study, we investigated the effects of vaginal administration of Bacteroides fragilis on the cloacal microbiota, vaginal transcriptome and metabolomics of chickens and evaluated the beneficial potential of B. fragilis. The results showed that B. fragilis treatment could affect the microbial composition of the cloaca. Transcriptome analysis found that the immune-related genes CCN3, HAS2, and RICTOR were upregulated, that the inflammatory genes EDNRB, TOX, and NKX2-3 were downregulated, and that DEGs were also enriched in the regulation of the inflammatory response, cellular metabolism, and synaptic response pathways. In addition, the differential metabolites were mainly related to steroid hormone biosynthesis, unsaturated fatty acid biosynthesis, and arachidonic acid metabolism, and we identified associations between specific differential metabolites and genes. Overall, this study provides a theoretical basis for the application of B. fragilis as a potential probiotic in livestock and poultry production.